STUDI LITERATUR: MENERAPKAN PEMBELAJARAN SOSIAL EMOSIONAL SEBAGAI PENINGKATAN HASIL BELAJAR KOGNITIF SEKOLAH DASAR - Muzaki, Alfian Nur; Rohmah, Aliya; Ngaini, Dwi Nur; Krismonita, Marenda Dias; Siswoyo, Andika Adinanda (Jurnal Media Akademik (JMA), 2025)
Aim of literature review study is examine social-emotional learning (SEL) can be used to enhance primary school pupils' cognitive learning results. By reviewing five pertinent scholarly journals, the study takes a qualitative approach. Results show that SEL improves students' social emotional capabilities while simultaneously having major positive impact on their academic achievement in classroom. Self-awareness, self-management, social awareness, relational skills, and responsible decision-making are the five SEL core competencies. Group conversations, role-playing, and cooperative projects that promote empathy, communication, teamwork, and learning motivation are ways that SEL is incorporated into classroom instruction. Providing a secure, encouraging, and welcoming learning environment, parents' and the community's support is vital, and teachers play a critical role as facilitators. Guarantee sustainable SEL practices, the evaluation also highlights the necessity of school policies and training. As a result, SEL becomes an essential teaching method for encouraging students' overall character development and raising their academic performance.